A COMPARATIVE STUDY OF VICRYL RAPIDE SUTURE VERSUS CHROMIC CATGUT SUTURE FOR EPISIOTOMY REPAIR - Samreena Akhtar Chohan,; Saima Altaf,; Kausar Inayat,; Seemab Zafar,; Nosheena Shabbir,; Shehnaz Sheeba, (Journal of Ayub Medical College Abbottabad, 2024)
Background: An episiotomy is a perineal incision performed to facilitate childbirth by enlarging the diameter of the vulvae outflow. Given the prevalence of long-term complications following episiotomy repair, this investigation employed vicryl rapide suture, a polyglactin analogue that induces reduced tissue reaction and is absorbed via hydrolysis (in contrast to chromic catgut suture). Produced from collagen, chromic catgut induces an inflammatory response within the tissues upon degradation by phagocytosis and proteolytic enzymes. There is disagreement regarding the superior suture material. This study was therefore designed to compare pain at 48 hours and analgesia requirement at 7th day in chromic catgut suture and vicryl rapide suture. The purpose of this study was to determine pain at 48 hours and analgesia requirement at 7th day between vicryl rapide suture and chromic catgut suture. Methods: This study was conducted at department of GYNAECOLOGY and OBSTETRICS at Shaikh Zayed Hospital Lahore. A total of 206 (103 in each group) females were enrolled in this study. Result: In this study the mean age of the cases in vicryl rapide group was 28.94 ± 3.50 and in chromic catgut group it was 29.05±3.43. A total of 103 (50%) female were enrolled in Group A and 103 (50%) were enrolled in Group B. In this study pain at 48 hours was found in 33 (32%) patients in vicryl rapide group and 52 (50.5%) in chromic catgut group p-value=0.007. Similarly, analgesia requirement at 7th day was found in 2 (1.9%) patients in vicryl rapide group and 26 (25.2%) patients in chromic catgut group with significant p-value <0.001. Conclusion: This study concluded that vicryl rapide was the best suture material for episiotomy repair, resulting in decreased pain after 48 hours and lesser need for analgesia by the seventh day.